Groundwater Salinity Distribution in Sub-District Kedung, District Jepara - Ilham Erie Maulana; Sudarmadji Sudarmadji (Indonesian Journal of Geography, 2016)
The groundwater salinity in Kedung Sub-district, near the coastal area, is the result of the salt water that comes into the aquifers and the salt water seepage from the surface. The broad groundwater salinity is because of the recent land condition that is resulted from the deposition in the ocean. The nature of the groundwater in-Sub-distric from all aquifers consists of 14% saline groundwater, 48% brackish groundwater and 38% fresh water. The number of community that has brackish until saline ground water property is 19.202 people, so that the domestic water need for the community is 1.344.378 liters/day. Such environmental condition makes the residents make some adaptation. The adaptation of the land use aspect is by making the western region as a fishponds region and the eastern one as a rice fields region. Adaptation in community activities is to fulfill the needs by working as farmers (on the rice fields, fish ponds or salt ponds) or as the fishermen. Adaptation is also made to minimize the threat of disasters, such as the manufacture of levees, weirs or dams and diversions to prevent the spread of tidal flooding.